NADPH Oxidase 4: A Potential Therapeutic Target of Malignancy - Gong, Shulei; Wang, Shiyang; Shao, Mingrui (Frontiers in Cell and Developmental Biology, 2022)
Reactive oxygen species (ROS) play a crucial role in the regulation of tumor occurrence and development. As a main source of ROS, NADPH oxidases are key enzymes that mediate electron transport within intracellular membranes. Of the NOX members that have been reported to be dysregulated in a wide variety of tumors, NOX4 is the member to be most frequently expressed. Numerous studies have elucidated that NOX4 gets involved in the regulation of tumor proliferation, metastasis, therapy resistance, tumor-stromal interaction and dysregulated tumor metabolism. In this review, we primarily discussed the biological function of NOX4 in tumorigenesis and progression of multiple cancer models, including its role in activating oncogenic signaling pathways, rewiring the metabolic phenotypes and mediating immune response. Besides, the development of NOX4 inhibitors has also been unraveled. Herein, we discussed the interplay between NOX4 and tumorigenesis, proposing NOX4 as a promising therapeutic target waiting for further exploration.